NEW SEDIMENTOLOGIC, PETROGRAPHIC, BIOSTRATIGRAPHIC AND STRUCTURAL DATA ON THE REITANO FLYSCH (MAGHREBIAN CHAIN, SICILY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
A sedimentologic, petrographic, biostratigraphic and structural study was carried out on the external ourcrops of the Reitano Flysch (Western Maghrebian Chain, Sicily) in order to clarify its age, relationships with its substratum and paleogeographic significance, all of which are still very controversial. The results of our analyses yielded some peculiar features of the external Reitano Flysch, namely; 1) the outcrops are characterized by vertical and horizontal variation in facies; 2) the facies and paleocurrent directions vary abruptly over short distances; 3) the sandstones are characterized by remarkably fresh volcanoclastic detritus, which is absent in the internal outcrops of the Reitano Flysch; 4) the deformation structures, though influenced by the differences in the lithology, are considered to be the result of transpression under a shear regime; 5) the boundary between the external Reitano Flysch and the underlying Polizzi Formation is stratigraphic; both formations have an Early Oligocene age. On the base of the above data, a new evolutionary scheme is tentatively proposed, where the internal Reitano Flysch represents a "satellite" basin and the exrernal Reitano Flysch is considered a small basin of pull-apart type.
Keywords: Sedimentology; Petrography; Biostratigraphy; Structural Geology; Reitano Flysch (Sicily).